Psycholinguistic Peculiarities of Non-Canonical (Personal) Religious Discourse - Савелюк, Наталія; Ткач, Тамара (Psiholìngvìstika, 2019)
Introduction. The article reveals universal and specific features of non-canonical religious discourse. Religious discourse is generally defined as the process of cognitive-speech activity in a religiously relevant social and communicative situation, which involves the reception, transmission and/or creation (compilation) of certain religious texts in a certain context; and as the current result of this activity, which creates the corresponding discursive picture (model) of the world. The main genre of religious discourse is prayer – canonical (institutionalized) and non-canonical (non-institutionalized, personal). Non-canonical prayer is defined as an appeal to God, the text of which may contain both canonical fragments and individual verbal formulations of the subject. Materials & Techniques of the Research. The sample of empirical research is 543 persons of different age, social status, from different regions of Western Ukraine. Due to the use in the first stage of «Methods for the Study of Religious Activity» (D. Smirnov) and subtraction of quartiles, the whole initial sample is divided into four sub-samples of persons with different levels of religious activity. In the second stage, the verbalization of non-canonical religious discourses was recorded. The thus obtained 543 texts were subjected to content-analytic procedures using the «Textanz» computer program. The methods of psychosemantic and psycholinguistic textual analysis are used as the basis for the mentioned processing and interpretation of results. Results. According to the results of the study, universal patterns of psycholinguistic structure of non-canonical religious discourse were identified, connected with the activation of the «I–You» system and the verbal explication of a certain personal request and gratitude. Some specific semantic variations of the corresponding discourse, due to the level of religious activity of the subject, are also revealed. It is stated, in particular, that at its higher levels, the number and, consequently, the importance of the tokens of the noun category «Spiritual, psychic life» («love», «heart», etc.) are increasing. This demonstrates the importance of prayer for high-religious individuals, not only as an external means of support, but as an effective psychological resource for self-control.